Estimating the Impact of Migration and Remittances on Agricultural Technology - Quinn, Michael A. (The Journal of Developing Areas, 2009)
The rapid growth of international migration and remittances has led to a wealth of research examining these trends. One of these lines of research attempts to determine the relationship between migration, remittances and the adoption of "Green Revolution" high yield variety (HYV) seeds. This literature proposes that migration and remittances may increase HYV use by reducing household risk and credit constraints. Given the large scale of both migration and remittances, getting an accurate measurement of these impacts is crucial to designing and implementing policies in rural areas. This paper examines the relationship between migration, remittances and agricultural technology. The credit and risk hypotheses are tested using data from the Mexican Migration Project. The main focus of the paper is examining the issue of endogeneity with respect to migration and remittances. When the probit approach is tested, evidence of endogeneity bias with respect to migration and remittances is found. The risk and credit hypotheses are then tested with two-stage and three-stage analyses, in order to address the problem of endogeneity. The results are found to be significantly different when methodologies are employed to deal with endogeneity; suggesting this is an issue that needs to be addressed. Overall, the results find some evidence to support both the credit and risk hypotheses; although the results for the risk hypothesis are more mixed.